The Juridical Review of Law Number 1 of Year 1974 on Marriage and the Compilation of Islamic Law Concerning Status of Different Religious Wedding Abroad - Rahmat Suhargon; Faulia Anggeraini (IHSA Institute, 2021)
The purpose of this study is to determine the legal status of interfaith marriages conducted abroad in terms of Law number 1 of year 1974 concerning Marriage and to determine the legal status of interfaith marriages abroad in terms of the Islamic Law Compilation. The method used in this research is the library research method. This study uses qualitative data. The data source used is the primary data source which comes from Law number 1 of year 1974 concerning Marriage, Compilation of Islamic Law, and related laws concerning the focus of the problem and secondary data sources sourced from books, journal articles, and other sources that support this research data. Data analysis in this research is information review, comparative study, and assessment study. The results of this study indicate that Indonesia's positive law, namely Law Number 1 of year 1974 concerning Marriage which applies nationally does not require interfaith marriages. Meanwhile, the Islamic Law Compilation clearly states that interfaith marriages occur, meaning that interfaith marriages do not get a legality from the Islamic Law Compilation.